A cloud-fog scalable video streaming architecture for multimedia internet of things devices. Issue 2 (9th May 2019) - Hsu, Tz-Heng; Wu, Lin-You
Cloud computing can be used to provide guaranteed quality of video services. On the other hand, fog computing can lower the transmission costs by using collaborative machine-to-machine and near-user edge communications. In this paper, a cloud-fog scalable video streaming architecture for multimedia internet of things (IoT) devices is proposed, where fog nodes can collaborate with the rented cloud servers for efficiently delivering the requiring video frames to multimedia IoT devices. The proposed architecture strengthens the stability of the video streaming transmission and improves the quality of service (QoS) of multimedia IoT services with cloud-fog computing techniques. Simulation results show that the proposed cloud-fog scalable video streaming architecture can provide smooth video streaming services to multimedia IoT devices with low-cost than traditional video streaming approaches.